UPAYA DAN IMPLIKASI PENYEDIAAN RUANG TERBUKA HIJAU (RTH) - Dadang Mashur; Zaili Rusli (Jurnal Kebijakan Publik, 2018)
Efforts and Implications of Green Open Space (RTH). The current urban problem hasbecome a complicated problem to overcome. Urban development leads to negative con- sequenceson several aspects, including environmental aspects. In the early stages of urban development, most of the land is green open space. However, there is a need for space to accommodate the population and its activities, the green space is likely to undergo conversion of land use to a wakearea. Most of its surface, especially in the city center, is covered by roads, buildings and others with very complex characters and different from the green open space characters. These are exacerbated by weak law enforcement and public awareness of urban spatial planning, causing frequent floodingin urban areas, high air pollution and increased social vulnerability (crime and social crisis), decreased public productivity due to stress due to limited public space which are available for social interaction,and cause congestion problems due to high side barriers in certain road segments.